Bilateral Posterior Subthalamic Area Deep Brain Stimulation for Essential Tremor: A Case Series - Sun, Xiaoyu; Huang, Luke; Pan, Yixin; Zhang, Chencheng; Wang, Tao; Li, Hongxia; Sun, Bomin; Ding, Jianqing; Wu, Yiwen; Li, Dianyou (Frontiers in Human Neuroscience, 2020)
BACKGROUND: Deep brain stimulation (DBS) of the posterior subthalamic area (PSA) provides a potentially effective treatment for medication-refractory essential tremor (ET). OBJECTIVE: To study the clinical benefits and adverse-event profile of bilateral PSA-DBS for refractory ET. METHODS: Seven patients with refractory ET underwent bilateral PSA-DBS surgery under general anesthesia between September 2017 and May 2018. Clinical outcome assessments, using the Essential Tremor Rating Scale, were performed at 1-, 6-, and 12-month follow-up, except for the last assessment of one patient who was followed up to 9 months. Analysis was focused on changes in patients’ motor symptoms and quality of life following surgery, along with documenting the adverse-event profile associated with the surgical PSA-DBS treatment. RESULTS: After surgery, patients’ motor symptoms, including upper limb tremor and head tremor, were improved by XX% and their quality of life by XX% at 1-month follow-up. The clinical benefits to patients were maintained at 6-month and last follow-up. Adverse side effects included dysarthria (n = 4), balance disorder (n = 2), and paresthesia of the right limb (n = 1). No tolerance effects were observed throughout the follow-up. CONCLUSION: Bilateral PSA-DBS seems to offer an effective and safe alternative treatment for medically intractable ET, warranting further research into its clinical utility, adverse-event profile, and comparative effectiveness.